ALGORITHMIZATION OF NON-COLLISION MOTIONS OF PLANAR POSITIONERS OF UNIVERSAL ASSEMBLY UNIT - V. V. Poliakovski; D. G. Begun; I. V. Dainiak (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The structure of universal assembly unit was described; the unit includes six or more planar positioners moving on one stator in the general workspace. The algorithm of non-collision displacements was proposed for the trajectory planning of simultaneous motion of several positioners; the algorithm is built on the analysis of trajectories, the configuration of forbidden zones and the priority rule, it is intended for implementation in the control system of assembly unit. The features and benefits of control system of servo-drives and precision motion systems which is realized using Ether-CAT technology were described.